Dermal bacterial LPS-stimulation reduces susceptibility to intradermal Trypanosoma brucei infection - Omar A. Alfituri; Enock M. Mararo; Pieter C. Steketee; Liam J. Morrison; Neil A. Mabbott (Scientific Reports, 2021)
Abstract Infections with Trypanosoma brucei sp. are established after the injection of metacyclic trypomastigotes into the skin dermis by the tsetse fly vector. The parasites then gain access to the local lymphatic vessels to infect the local draining lymph nodes and disseminate systemically via the bloodstream. Macrophages are considered to play an important role in host protection during the early stage of systemic trypanosome infections. Macrophages are abundant in the skin dermis, but relatively little is known of their impact on susceptibility to intradermal (ID) trypanosome infections. We show that although dermal injection of colony stimulating factor 1 (CSF1) increased the local abundance of macrophages in the skin, this did not affect susceptibility to ID T. brucei infection. However, bacterial LPS-stimulation in the dermis prior to ID trypanosome infection significantly reduced disease susceptibility. In vitro assays showed that LPS-stimulated macrophage-like RAW264.7 cells had enhanced cytotoxicity towards T. brucei, implying that dermal LPS-treatment may similarly enhance the ability of dermal macrophages to eliminate ID injected T. brucei parasites in the skin. A thorough understanding of the factors that reduce susceptibility to ID injected T. brucei infections may lead to the development of novel strategies to help reduce the transmission of African trypanosomes.